2019
DOI: 10.3390/nano9020185
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Mediated Electroless Deposition of Gold Nanoparticles for Highly Uniform and Efficient SERS Enhancement

Abstract: A seed-mediated electroless deposition (SMED) approach for fabrication of large-area and uniform gold nanoparticle films as efficient and reproducible as surface-enhanced Raman scattering (SERS) substrates was presented. This approach involved a seeding pretreatment procedure and a subsequent growth step. The former referred to activation of polylysine-coated glass slides in gold seed solution, and the latter required a careful control of the reactant concentration and reaction time. With the aid of gold seeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…It has been reported that the electromagnetic behaviors of AgNP arrays are virtually enhanced due to the spaces between the particle arrays because parts of the two- and three-dimensional (2D and 3D, respectively) hot-junctions formed are smaller than 10 nm. Fabrication methods of AuNPs include electron beam lithography [16], chemical vapor deposition [17], and the oxidation-reduction reaction [18]. Meanwhile, there is growing interest in the use of biodegradable and sustainable materials [19] for SERS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the electromagnetic behaviors of AgNP arrays are virtually enhanced due to the spaces between the particle arrays because parts of the two- and three-dimensional (2D and 3D, respectively) hot-junctions formed are smaller than 10 nm. Fabrication methods of AuNPs include electron beam lithography [16], chemical vapor deposition [17], and the oxidation-reduction reaction [18]. Meanwhile, there is growing interest in the use of biodegradable and sustainable materials [19] for SERS.…”
Section: Introductionmentioning
confidence: 99%
“…This allows to obtain a SERS signal from at least one or two hot spots in 78% or 37% of the measurements, respectively ( Figure S6a). However, as already mentioned by Crawford et al 28 increasing the laser spot size above the objective-de ned size requires speci c technical equipment to widen the laser spot and concomitantly requires an increase in the laser power, which is not possible in all commercially available Raman spectrometers.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the reproducibility of SERS signals can be highly dependent of the size of the laser spot. Sampling errors or undersampling occurs when the size of the analysed area is below that needed to reliably represent the composition of the sample 28 . Heterogeneous SERS substrates therefore require an illumination with large laser spot sizes to obtain reliable results.…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentration of activator or too long immersion time lead to improper activation which probably cause poor metallic bonding. There are many commercial catalysts that can be used in the activation process as showed in Table 8 [ 282 , 283 , 284 , 285 ]. Generally, the electroless plating is regarded as a dehydrogenation reaction since the hydrogen may develops simultaneously with metal reduction.…”
Section: Electroless Plating Proceduresmentioning
confidence: 99%